HUBUNGAN KEBIASAAN MEROKOK DI DALAM RUMAH DENGAN KEJADIAN PENYAKIT INFEKSI SALURAN PERNAPASAN AKUT (ISPA) PADA BALITA DI PUSKESMAS BATURETNO I - Budi Kristanto; Ambrosius Setya Widri Hanggara (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2017)
Background : deaths due to ARI disease in infants reaching 12.4 million in toddlers 0-5year age group every year worldwide, two thirds are babies, that is 0-1 years old and80.3% of deaths occur in developing countries (Kemenkes , 2010). The prevalence ofARI occurrence in Indonesia is 25.0% (Riskesdas, 2013: 23). Smoking habits of parentsin the home make toddlers as passive smokers are always exposed to cigarette smoke.Research purposes : to determine the relationship between exposure to secondhandsmoke with the incidence of acute respiratory infections in infants.Subject : toddlers who checked at Puskesmas Baturetno 1 in February-March 2017 werediagnosed with acute respiratory infection.Methods : this research use correlation research design with cross sectional method. Thepopulation is all parents of children under five who checked their children to Baturetno IPuskesmas in February and March with an acute respiratory infection diagnosis, a total of20 respondents. Control group of children who did not experience acute respiratory tractinfection of 20. Researchers used questionnaire tools. Data obtained then tabulated andanalyzed using SPSS 16 for Windows.Results : 15 children (75%) were exposed to cigarette smoke and 5 children (25%) werenot exposed to cigarette smoke. There was an association between ARI occurrence andexposure of cigarette smoke to under-five children at Puskesmas Baturetno I with p:0.011 <Î±: 0.05Conclusion : There is a correlation between ARI occurrence and exposure of tobaccosmoke in infants at Puskesmas Baturetno I.Keywords: smoking, acute respiratory infections, less than five years